Factors influencing online banking adoption: the case of academicians in Malaysian technical University network (MTUN) - Al-Subari, Saleh Nasser; Mohamed Zabri, Shafie; Ahmad, Kamilah (Advanced Science Letters, 2018)
Advancement of technology saw the evolution of how banking activities being conducted. Online banking for example, has created new approach of banking activities around the globe. This study was conducted to investigate and determine factors influencing online banking adoption among academicians in Malaysia. The selection of factors was developed based on extended Technology Acceptance Model (TAM). TAM is the most widely applied model in the field of technology adoption. TAM investigates the adoption of technology based on its Perceived Usefulness and Perceived Ease of Use. Government support was included as an extension of the original model mainly because of its direct influence on the existence of the online banking itself. These factors were categorized as the independent variables in this study while online banking adoption as the dependent variable. Data for this research were collected from survey questionnaires, distributed to the target population of academicians at four higher education institutions listed under Malaysian Technical University Network (MTUN) in Malaysia. Data collected were analyzed using Statistical Package for Social Science (SPSS) software. Correlation and regression technique was employed to study factors influencing online banking adoption among respondents, Results of the analysis shows that Perceived Usefulness and Perceived Ease of Use found to be significant factors while Government Support is found to be not a significant factor in influencing the adoption of online banking among the respondents. This study has shed new knowledge for the research in the area of technology adoption particularly in Malaysia.